PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN LABUHANBATU - Ahmad Rivai Siregar; Ali Sahbana Edi Lubis; Syafrizal Effendi; Sondang Roma Elda T; Delita . (Universitas Islam Sumatera Utara, 2021)
The problem of this research is: How does the motivation, organizational culture and work discipline on the performance of employees. This study aims to determine the effect of motivation, organizational culture and work discipline on employee performance. With the probability sampling technique determined by the Slovin formula, the sample in this study was 64 people. The motivation variable partially has a positive influence on employee performance; The organizational culture variable partially has a positive influence on employee performance; The work discipline variable partially has a positive influence on employee performance; Motivation, organizational culture and work discipline simultaneously have a positive and significant influence on employee performance.